Analysis of Anisotropic Strength and Wellbore Unstable Zone in Shale Formation Relating to Water Content. (8th February 2023) - Qiu, Linjie; Zhang, Min; Wang, Yansen
Abstract : During oil and gas exploitation, wellbore stability has always been the focus of many scholars. Instability of wellbore will lead to washouts, breakout, stuck pipe, mud loss, and so on, even the abandon of the well. Shale rock is widely distributed in nature and must be taken into account in some rock engineering applications. In order to evaluate the strength anisotropy and the influence of moisture content of the wellbore integrity, the LMX outcrops are divided into three groups to carry out triaxial strength experiment. Based on the fitting method of collaborative search, the strength parameters of different moisture contents are determined; then, the effect of strength anisotropy and the moisture content of the LMX reservoir on wellbore collapse pressure and wellbore integrity are investigated. The results show that shale strength, especially cohesion, is more sensitive to the influence of water. With the increase of water content, the inclination angle of the minimum value obtained by shale strength is deviated to the left, and the collapse pressure and instability area increase significantly. At the same time, it is necessary to adjust the direction of borehole drilling to avoid the occurrence of the zone of bedding slip instability in the direction of the minimum in situ stress, and the inversion of in situ stress should be corrected by considering the effect of bedding on the location of the maximum in situ stress. The study on the effects of bedding and water content on the instability zone can provide suggestions and guidance for the optimization of borehole trajectory, the control of bottom hole safety pressure, the inversion of in situ stress, and the drilling and completion of wells.